Acacia sieberiana Effects on Soil Properties and Plant Diversity in Songa Pastures, Rwanda. (4th November 2013) - Mugunga, C. P.; Mugumo, D. T.
Abstract : Effects of A. sieberiana trees on soil properties and plant diversity were investigated in Songa pastures, Rwanda. Tree characteristics and crown architecture of A. sieberiana were studied. Soil properties were assessed and plants were identified under and away from tree crowns. Counts of individual plants/species were done only under tree crowns. Nitrogen, P, and K were analysed in the soil, grass, and A. sieberiana leaves. Plant diversity was determined using Simpson's diversity index. Data were subjected to ANOVA. Soil organic carbon (SOC), cation exchange capacity (CEC), Ca 2+, N and pH, and plant diversity were higher in soils under tree canopies than in open areas. Tree leaves were significantly richer in N and poorer in P and K as compared to grasses. Tree crowns grew wider and horizontal and developed intertwined secondary branching, reducing light intensity to as low as 38% under tree canopies compared to the open pasture. At 3 trees/ha stocking, A. sieberiana trees shaded 0.18 ha and herbaceous plants and grasses unpalatable to livestock dominated under tree canopies. A tradeoff of A. sieberiana tree value versus the loss of palatable grass due to tree presence needs to be assessed to decide whether the trees should be included in pastures and if yes, the apporpriate stocking identified.